Growth curves of Nile tilapia (Oreochromis niloticus) strains cultivated at different temperatures - Santos, Vander Bruno Dos; Mareco, Edson Assunção [UNESP]; Dal Pai Silva, Maeli [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
Growth of Red, GIFT and Supreme Nile tilapia strains were evaluated. Fish were cultivated in indoor recirculation systems in 0.5 m³ tanks with controlled temperatures of 22, 28 and 30°C. Random samples of 20 fish from each strain (10 fish tank-1) were weighed at day 7, 30, 60, 90 and 120. Exponential model (y=AeKx) and Gompertz model (y = Aexp(-Be-Kx)) were fitted and the estimates parameters were obtained by Weighted Least Squares. At 22°C, Red, GIFT and Supreme strain presented similar growth and fit of exponential model. GIFT and Supreme strain presented higher growth rate at 30°C of cultivation when compared to Red strain. Temperature influences weight and age at the inflection point. The temperature of cultivation influences the growth description of Red, GIFT and Supreme tilapia strains. It changes the age and weight at inflection point and the qualities of growth model fits, changing the variation of the batch.

Avaliou-se o crescimento de tilápias das linhagens Vermelha, GIFT e Supreme. Os peixes foram cultivados em sistemas de recirculação em tanques de 0,5 m³ nas temperaturas de 22, 28 e 30°C. Amostras aleatórias de 20 peixes de cada linhagem (10 peixes tanque-1) foram pesadas aos 7, 30, 60, 90 e 120 dias de cultivo. O modelo exponencial (y = AeKx) e o modelo de Gompertz (y = Aexp(-Be-Kx)) foram ajustados e as estimativas dos parâmetros foram obtidas por Quadrados Mínimos Ponderados. A 22°C o crescimento das linhagens Vermelha, GIFT e Supreme e o ajuste do modelo exponencial foram semelhantes. As linhagens GIFT e Supreme apresentaram maior taxa de crescimento a 30°C quando comparadas à linhagem Vermelha. Pode-se observar influência da temperatura no peso e idade ao ponto de inflexão. A temperatura de cultivo influencia a descrição do crescimento de tilápias das linhagens Vermelha, GIFT e Supreme, alterando a idade e o peso ao ponto de inflexão, a qualidade dos ajustes dos modelos e a uniformidade dos lotes.
Curvas de crescimento de linhagens de tilapias do Nilo (Oreochromis niloticus) cultivadas em diferentes temperaturas
Keywords: modelo exponencial; taxa de crescimento; Supreme; GIFT; tilápia vermelha; modelo ponderado; exponential model; growth rate; supreme; GIFT; red tilapia; weighted model